EFEKTIVITAS KURSUS CALON PENGANTIN DALAM MEMBERI PEMAHAMAN KONSEP KELUARGA SAKINAH - Aris Aris; Budiman Budiman; Zulkifli Zulkifli (DIKTUM: Jurnal Syariah dan Hukum, 2017)
Abstract: This paper is intended to reveal how the mechanism and implementation of bride and groom courses in the Office of Religious Affairs (KUA) Kecamatan Duampanua Pinrang District and the factors inhibiting and supporting the implementation of bride and groom courses in the Office of Religious Affairs (KUA) Duampanua District Pinrang District and how the bride's understanding of the the concept of sakinah family. The effectiveness of the bride and groom course has not been fully run in the community with various inhibiting factors, so the bride and groom have not fully understood the material about the concept of sakinah family that has been poured into the bride's course process.